CHEMICAL COMPOSITION OF THE SWIMMING CRAB PORTUNUS PELAGICUS LINNAEUS - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
The results of the chemical analyses (moisture, ash, fat and protein) of themale and female crab of Portunus pelagicus Linnaeus with shell and meat are givenin this paper. The differences in th-s composition between the whole crab andedible meat and the economic uses of crab are also given.